Strategic Role of Hr In It Industry: Exploring the Key Role of HR in the IT Industry (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Human Resource Management (HRM) is a relatively newapproach to managing people in any organisation. People are considered the keyresource in this approach. it is concerned with the people dimension in management of an organisation. Since anorganisation is a body of people, their acquisition, development of skills,motivation for higher levels of attainments, as well as ensuring maintenance oftheir level of commitment are all significant activities. These activities fallin the domain of HRM.Human Resource Management is a process, which consists offour main activities, namely, acquisition, development, motivation, as well asmaintenance of human resources. Scott, Clothier and Spriegel have defined HumanResource Management as that branch of management which is responsible on astaff basis for concentrating on those aspects of operations which areprimarily concerned with the relationship of management to employees andemployees to employees and with the development of the individual and thegroup.